2019
DOI: 10.1515/jisys-2018-0365
|View full text |Cite
|
Sign up to set email alerts
|

A Color Image Encryption Technique Based on Bit-Level Permutation and Alternate Logistic Maps

Abstract: The paper presents an approach to encrypt the color images using bit-level permutation and alternate logistic map. The proposed method initially segregates the color image into red, green, and blue channels, transposes the segregated channels from the pixel-plane to bit-plane, and scrambles the bit-plane matrix using Arnold cat map (ACM). Finally, the red, blue, and green channels of the scrambled image are confused and diffused by applying alternate logistic map that uses a four-dimensional Lorenz system to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Values of of Black and White images are extremely good, while those of House are worse. The quality for each of permutation and diffusion processes in this example is better than those in recent works, for example, Reference [ 74 , 75 ]. Chosen-plaintext and chosen-ciphertext attacks In this work, the permutation and diffusion processes are considered separately.…”
Section: Example and Simulationmentioning
confidence: 65%
See 1 more Smart Citation
“…Values of of Black and White images are extremely good, while those of House are worse. The quality for each of permutation and diffusion processes in this example is better than those in recent works, for example, Reference [ 74 , 75 ]. Chosen-plaintext and chosen-ciphertext attacks In this work, the permutation and diffusion processes are considered separately.…”
Section: Example and Simulationmentioning
confidence: 65%
“…The quality for each of permutation and diffusion processes in this example is better than those in recent works, for example, Reference [ 74 , 75 ].…”
Section: Example and Simulationmentioning
confidence: 65%
“…To enhance the security of algorithm the shuffled image is again encrypted by the diffusion process. In this stage, change the pixel values of every shuffled image using one of the discrete chaotic systems such as Lorenz or Lu (Bisht et al, 2020;Amigo et al, 2007). Finally, combined output of previous step results in encrypted image or also known as cipher image.…”
Section: Encryption Algorithmmentioning
confidence: 99%
“…Wang et al [34] proposed a multi-dynamic segmented coupled mapping network with well chaotic behavior and designed an image encryption scheme based on it, which satisfies the cryptographic requirements. In [35], Dua et al suggested a cryptographic operation for color images using alternate logistic maps. The parameters of the Arnold cat mapping were generated with logistic sine maps and logistic tent maps, the produced random sequences were applied to the bit-plane permutation, followed by combining the bit planes into pixel matrices, which were then scrambled and diffused by the chaotic sequences generated from alternate logistic maps.…”
Section: Introductionmentioning
confidence: 99%